Clinicopathological Proficiency in the Diagnosis of Kaposi's Sarcoma. (30th May 2012) - van Bogaert, Louis-Jacques
Abstract : Background . The prevalence of Kaposi's sarcoma (KS), an AIDS-defining illness, has increased in parallel with the HIV/AIDS epidemic. The presence of violaceous skin lesions should raise suspicion of KS. However, especially on dark skin, KS mimics a variety of non-KS skin conditions. Histologically, there is a wide range of expressions of KS and a large number of mimickers. For all these reasons, a HHV-8 immunohistochemically biopsy-proven diagnosis of KS should be the gold standard. Methods . Prospective study of 490 consecutive skin biopsies from the general community in the Limpopo Province of South Africa, from April 2010 through December 2011. Results. The clinical discordance rate (over-/underdiagnosis of KS) was 30.5%; the histological discordance rate was 9.2%. Conclusion . Because of the magnitude of diagnostic error, both clinical and histological, all clinical lesions suspicious of KS should be biopsied and HHV-8 LAN-1 immunophenotyped.